Reminder and Online Booking Features at Android-Based Motorcycle Repair Shop Marketplace - Mahendra, Wayan Dony; Sukarsa, I Made; Cahyawan, AA.Kt. Agung (Universitas Negeri Semarang, 2020)
Generally, vehicle service is a must for the vehicle owner. However, due to tight work routines, people often forget to service their vehicles. In addition, the service process is still using a manual system, such as taking a queue number which leads to the long queue of the service time. An Android-based Motorcycle Repair Shop Information System provides a solution to remind people to do a regular service on their vehicles with a reminder feature and make online bookings. Â The system development uses the SDLC (System Development Life Cycle) method. The implementation process requires an Android smartphone and a computer device by using MySQL as data storage, Firebase as a notification sender, React native and Visual Studio Code are used for developing the system. The results of the UAT test (user acceptance testing) from 20 users show 55,8% answered agreeÂ to the display, features and flow of the system, 39,5% answered strongly agreeÂ to the three question parameters, and 4,7% answered disagree with the flow and display of the system.